Social capital in post-disaster "Haiyan" the case of the bunkhouse evacuees - Colasito, Carmen Mae B.; Pomida, Kristian Ray R.; Tumandao, Donabel S. (2015)
Typhoon Haiyan which is the deadliest and most destructive typhoon to hit the Philippines caused the displacement of 4.1 million people and is considered to be the largest displacement in 2013. In Tacloban City, which is considered the ground zero of Typhoon Haiyan, 15,000 families were displaced and most of them are now staying in the bunkhouses.